PENGEMBANGAN SISTEM INFORMASI PENJADWALAN TALK SHOW PT RADAR LAMPUNG TV DAN PENAMBAHAN UTILITAS NOTIFIKASI VIA SMS CENTER BERBASIS ANDROID - Rizki Ahmad Muzakir; Dwi Sakethi; Rizky Prabowo (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
The topic of this research is the talk show scheduling information system that still needs to be developed with the addition of notification features. The development of the PT Radar Lampung TV Talk Show Scheduling Information System and the Addition of Notification Utility Via SMS Center based on Android is here to support the performance of the Talk Show scheduling information system so that it can work optimally. The purpose of this study is to develop a scheduling information system application and schedule notification utility via an Android-based SMS center. The Android-based SMS center notification application was developed using the Water Fall method and the JAVA and XML programming languages based on Android. After the application has been developed, then Black Box Testing is carried out on the Android-based SMS center notification application. The test results show that all features can run according to their functions.